Global incidence and mortality of pancreatitis in women of childbearing age from 1990 to 2021 - Wenkai Jiang; Ru He; Huiqi Sun; Tianxin Zhao; Xinru Liu; Wence Zhou (Scientific Reports)
Abstract To analyze the global burden of pancreatitis in women of childbearing age (WCBA) at the global, regional and national levels from 1990 to 2021. Data for pancreatitis incidence and deaths in females aged 15 to 49 years were downloaded from the Global Burden of Disease 2021 database. Estimated annual percentage changes (EAPCs) were calculated to describe the temporal trends. In 2021, the global numbers of incident cases and deaths of pancreatitis in the WCBA were 505,012 (409,536 to 627,684) and 7,002 (5,647 to 8,857), respectively. From 1990 to 2021, the global incidence and death rates of pancreatitis in the WCBA showed downward trends, with EAPCs of -0.15 (-0.21 to -0.09) and − 0.42 (-0.58 to -0.26), respectively. The most significant decreases in incidence and death rates were observed among females aged 40 to 44 years. Eastern Europe had the highest incidence and death rates in 2021. Countries with high socio-demographic index (SDI) showed the highest incidence rate, while showed greatest decrease in incidence during the past 32 years. The global pancreatitis incidence and death in WCBA has decreased since 1990, but the incidence is still high in countries with high-SDI. More efficient public health measures are needed to reduce the burden of pancreatitis.